Rozwiąż

a ) - 2,8 x (-1) x (-1,1)=

b ) 1,2 x (1,2)x (-2)=

c ) - 1,1 x (-11,1)x (-1,11)=

d )-2 x (-4,4) x (-1) x (-3,3)=

e ) -2 ¹/₂ x (-0,6) x 2 ⅖ 2 x (- 1 ¹/₉ ) =

f )- 3 ¾ x (-3 ⅗ ) x (-0,625) x (-1,4)=

g )-2 ³/₄ x (-1,5) x (-3¹/₃) x (-0,6) x (-1)=

h ) - ⁸/₃ x (-3,14) x (-1 ⁵/₇) x (-1) x [-(-14)] =

plis jak najszybciaj

2

Odpowiedzi

Najlepsza Odpowiedź!
2009-11-24T14:30:41+01:00
A ) - 2,8 x (-1) x (-1,1)= -3,08

b ) 1,2 x (1,2)x (-2)= -2,88

c ) - 1,1 x (-11,1)x (-1,11)= -13,5531

d )-2 x (-4,4) x (-1) x (-3,3)= 29,04

e ) -2 ¹/₂ x (-0,6) x 2 ⅖ x (- 1 ¹/₉ ) = -3,999

f )- 3 ¾ x (-3 ⅗ ) x (-0,625) x (-1,4)= -11,8125

g )-2 ³/₄ x (-1,5) x (-3¹/₃) x (-0,6) x (-1)= -8,2491

h ) - ⁸/₃ x (-3,14) x (-1 ⁵/₇) x (-1) x [-(-14)] = -83,52
1 5 1
2009-11-24T14:41:25+01:00
A ) - 2,8 x (-1) x (-1,1)=2,8*(-1,1)=-3,08

b ) 1,2 x (1,2)x (-2)=1,44*(-2)=-2,88

c ) - 1,1 x (-11,1)x (-1,11)=-13,542

d )-2 x (-4,4) x (-1) x (-3,3)=29,04

e ) -2 ¹/₂ x (-0,6) x 2 ⅖ 2 x (- 1 ¹/₉ ) =jakiś błąd chyba

f )- 3 ¾ x (-3 ⅗ ) x (-0,625) x (-1,4)=-3,75*(-3,6)*(-0,625)*(-1,4)=11,8125

g )-2 ³/₄ x (-1,5) x (-3¹/₃) x (-0,6) x (-1)=2,475*(-3⅓)=-22,5

h ) - ⁸/₃ x (-3,14) x (-1 ⁵/₇) x (-1) x [-(-14)] =-43,96*32/7=200,96
1 5 1